SOLUSI-SOLUSI PERIODIK PADA PERLUASAN FRACTIONAL VAN-DER POL TAK LINEAR - Waluya, S Budi (MATEMATIKA, 2005)
In this paper will be studied a Generalized Non Linear Rayleigh Oscillator. It will be shown that the recently developed perturbation method based on integrating factors can be used to approximate first integrals and periodic solutions. Not only approximations of first integrals will be given, but it will also be shown how in a rather efficient way the existence and stability of time-periodic solutions can be obtained from these approximations.